2016
DOI: 10.1177/1045389x16649449
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective multi-objective optimal positioning of magnetorheological dampers and active actuators in large nonlinear structures

Abstract: The optimal number and location of control devices not only play a major role in an effective structural control system but also lead to a cost-effective design. This article presents a multi-objective optimization method based on a new genetic algorithm for simultaneous finding of the optimal number and placement of actuators and magnetorheological dampers, in active and semi-active vibration control of structures. The proposed strategy considers three objective functions to be minimized through optimization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…GA developed by Holland (1975) is a powerful and capable optimization tool which has been used to generate useful solutions for complicated optimization problems in different fields of engineering. In designing structural control systems, GAs have been previously applied for optimal design of fuzzy controllers (Yan and Zhou, 2006), determining the optimum parameters of TMDs (Hadi and Arfiadi, 1998; Mohebbi and Joghataie, 2012), or MTMDs (Mohebbi et al, 2015b) for linear and nonlinear frames, designing optimal MR dampers (Xue et al, 2011), optimal design of AMDs (Mohebbi et al, 2015c) as well as optimal design and placement of sensors or actuators on structures for active control of structures (Abdullah et al, 2001; Askari et al, 2017; Joghataie and Mohebbi, 2012).…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…GA developed by Holland (1975) is a powerful and capable optimization tool which has been used to generate useful solutions for complicated optimization problems in different fields of engineering. In designing structural control systems, GAs have been previously applied for optimal design of fuzzy controllers (Yan and Zhou, 2006), determining the optimum parameters of TMDs (Hadi and Arfiadi, 1998; Mohebbi and Joghataie, 2012), or MTMDs (Mohebbi et al, 2015b) for linear and nonlinear frames, designing optimal MR dampers (Xue et al, 2011), optimal design of AMDs (Mohebbi et al, 2015c) as well as optimal design and placement of sensors or actuators on structures for active control of structures (Abdullah et al, 2001; Askari et al, 2017; Joghataie and Mohebbi, 2012).…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…For the same purpose Liu et al [12] used a discrete nonlinear optimization method and genetic algorithm. Askari et al [13] used multi-objective genetic algorithm in active control and magneto rheological dampers in semi-active control simultaneously. From the above discussion, it is found that most of the research done on irregular structures is based on their performance in a seismic event and the seismic structural control of irregular structures is yet to be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivities of the four optimization criteria with respect to different earthquake records were explored. Askari et al found the optimal number and placement of actuators and magnetorheological dampers in active and semiactive vibration control of structures, simultaneously, using a multiobjective optimization method based on a new GA.…”
Section: Introductionmentioning
confidence: 99%